Obtaining and characterization of Mixed Oxides of 1-xSrxMnO3+-8 - Vásquez, Carlos (2001)
Mixed oxides of the La, Sr MnO, ± (x=0.0-0.5) series were prepared by the citrate method. The characterization was carried out structurally by X-ray diffraction (XRD) and elementally by inductive plasma coupling.(ICP). The Mn/Mn" ratio of the oxide was determined by iodometry. The specific area of ​​the powder sample wasdetermined by BET. The electronic transport properties for different levels of La substitution were done at different temperatures between 300-700 K. The characterization results show us that our manufacturing technique produces oxides of the La, Sr MnOs type with favorable properties to be used as cathodes in fuel cells.